Potency of Visual Resources on Secondary School Students Educational Attainment in Social Studies in Ekiti State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2025)
The study investigatedpotency of visual resources on secondary school students’ educational attainment in social studies in Ekiti state, Nigeria. Quasi-experimental design of pre-test, post-test, control groups design was adopted. The population of the study consisted of all Junior Secondary School III students in Ekiti State. The sample for the study consisted of 155 JSS III students who were selected from four secondary schools in Ekiti State using multi-stage sampling procedure. The two research instruments were used such as lesson notes on Social Studies and Social Studies Performance Test (SSPT). The face and content validity of the instruments were ensured by Social Studies and Test and Measurement experts. The reliability of the instrument was determined through test-retest method.  The scores of the sampled students were analysed using the Pearson Product Moment Correlation Coefficient Analysis. A reliability coefficient of 0.85 was obtained. The research hypotheses were tested a 0.05 level of significance.  Findings found thatthere is a significant difference in the pre-test and post-test scores of Social Studies students when virtual resources were used. This study concluded that using visual resources for teaching Social Studies students is more effective than conventional methods of teaching as the performance of students taught with visual resources was better than their counterparts who were not taught with it. The study recommended that to improve Social Studies students’ academic performance, the use of visual resources should be encouraged in teaching Junior secondary schools’ students in Ekiti State. The school authority should organise in-service training for retraining of Social Studies teachers through seminars to update their knowledge and create awareness on the relevance of instructional resource meant for teaching Social Studies students.